KH Khoiron Syu'aib's Da'wah in Supporting the Career Transition of Ex-Costs in the Ex-Localization of Bangunsari Surabaya - Azzah Fatin, Risma; Azka, Ibnu (Al-MUNZIR, 2024)
This research aims to analyze KH Khoiron Syu'aib's da'wah strategy in supporting the career transition of former commercial sex workers (PSK) in the former Bangunsari localization, Surabaya. The government's closure of Bangunsari prostitution localization had a significant impact on former prostitutes who lost their livelihoods. In this context, da'wah plays an important role in providing moral, spiritual, and practical support to help them transition to a more dignified profession. This research uses a qualitative method to explore the da'wah strategy implemented by KH Khoiron Syu'aib. Data was collected through interviews with KH Khoiron Syu'aib, a former prostitute, and local community leaders. Direct observation and documentation were also carried out to complete the data. The results of this research show that KH Khoiron Syu'aib uses a holistic and comprehensive da'wah approach, including spiritual aspects, skills development, economic empowerment, and psychosocial support. Through regular recitations, skills training and economic empowerment programs, KH Khoiron Syu'aib has succeeded in increasing the awareness and ability of former prostitutes to switch to other, more dignified professions. Apart from that, the psychosocial support provided also helps former prostitutes overcome social stigma and increase their self-confidence. This research concludes that KH Khoiron Syu'aib's da'wah strategy is effective in supporting the career transition of former prostitutes in the former Bangunsari localization. A holistic and comprehensive approach is the key to success in changing the lives of former prostitutes and improving their welfare. It is hoped that these findings can become a reference for similar empowerment programs in other regions, as well as contributing to the development of a more effective and sustainable da'wah model in overcoming the social and economic problems faced by former prostitutes in Indonesia.Keywords: Career transition of prostitutes, Da'wah, Former Bangunsari localization, KH Khoiron Syuaib